2018
DOI: 10.1016/j.gloenvcha.2017.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Integrated assessment of international climate mitigation commitments outside the UNFCCC

Abstract: In the Paris Agreement under the United Nations Framework Convention on Climate Change (UNFCCC), for the first time, non-state actors were addressed in the international negotiations and were explicitly invited to act on climate change. Indeed, there are many transnational emission reduction initiatives (TERIs) outside the UNFCCC, driven by non-state actors or national governments, which aim at reducing greenhouse gas (GHG) emissions. Using an Integrated Assessment Model (IAM), this study assessed the potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 20 publications
2
55
0
Order By: Relevance
“…Our study extends previous assessments about the development of climate and energy policy mixes [23,[24][25][26], including studies of measures and commitments by non-state actors [27,28]. 9 Notably, these efforts have focused on specific aspects of climate policy (e.g.…”
Section: Introductionsupporting
confidence: 52%
“…Our study extends previous assessments about the development of climate and energy policy mixes [23,[24][25][26], including studies of measures and commitments by non-state actors [27,28]. 9 Notably, these efforts have focused on specific aspects of climate policy (e.g.…”
Section: Introductionsupporting
confidence: 52%
“…On a global level, there are few studies that have aggregated the GHG mitigation potential of individual NSA commitments. Roelfsema et al (Roelfsema et al, 2018) projected that the commitments reported to CDP, C40 Cities and Covenant of Mayors (the present Global Covenant of Mayors) would together lead to a reduction of about 1.3 GtCO 2 e/year compared to a no-policy baseline by 2030. While Roelfsema et al (2018) and our analysis used different baselines, we find the calculated GHG mitigation potential values to be comparable to our results (1.2-2.0 GtCO 2 e/year by 2030).…”
Section: Comparison Of Results With Earlier Studiesmentioning
confidence: 99%
“…Roelfsema et al (Roelfsema et al, 2018) projected that the commitments reported to CDP, C40 Cities and Covenant of Mayors (the present Global Covenant of Mayors) would together lead to a reduction of about 1.3 GtCO 2 e/year compared to a no-policy baseline by 2030. While Roelfsema et al (2018) and our analysis used different baselines, we find the calculated GHG mitigation potential values to be comparable to our results (1.2-2.0 GtCO 2 e/year by 2030). The Global Covenant of Mayors estimates a 1.4 GtCO 2 e/year emissions reduction by 2030, compared to a current policy baseline with a modelling start year of 2010 (GCoM, 2018a).…”
Section: Comparison Of Results With Earlier Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some doubt their effectiveness (e.g., Michaelowa & Michaelowa, ) or stress their dependency on state‐based forms of governance (e.g., Bulkeley et al, ; Hickmann, ), yet others assert that nonstate actions will contribute to complexity, fragmentation, and possibly undermine governance legitimacy and accountability (Kuyper, Linnér, & Schroeder, ). A growing number of studies, however, take an optimistic, if cautious, view that nonstate action could bridge governance gaps (e.g., Graichen et al, ; Hsu, Cheng, Weinfurter, Xu, & Yick, ; Hsu, Moffat, Weinfurter, & Schwartz, ; Roelfsema, Harmsen, Olivier, Hof, & Van Vuuren, ; Tosun & Schoenefeld, ). While there has been growing optimism, and emphasis on potential and positive signals, few studies look at whether, and under which circumstances, optimistic expectations can be realized.…”
Section: Introductionmentioning
confidence: 99%